The effects of age upon the expression of three miRNAs in muscle stem cells isolated from two different porcine skeletal muscles - Redshaw, Zoe; Sweetman, Dylan; Loughna, Paul (Elsevier, 2014)
Aging is associated with a gradual loss of skeletal muscle mass and an impaired ability of this tissue to compensate for trauma. Studies in rodents and humans have also shown that resident stem cells within muscle have a reduced ability to proliferate and differentiate. In this study muscle stem cells have been isolated from two muscles, the diaphragm (DIA) and the semimembranosus (SM), from young and old pigs. The levels of three micro-RNAs (miRNAs) were measured when cells were in a proliferative phase and after 24 and 72 h in differentiation medium. All three miRNAs are abundant in skeletal muscle with miR-1 and miR-206 known to regulate myogenic differentiation and miR-24 is involved in cell cycle regulation. The levels of expression of Pax7 and the myogenic regulatory factors MyoD and myogenin were also measured. There were marked differences in expression of all three miRNAs between the two age groups. Both miR-1 and miR-206 were reduced in the cells from the older animals. In contrast miR-24 expression was significantly higher in cells from older animals under differentiation conditions. There were also significant differences in the relative expression of all three miRNAs between cells from the SM and DIA in both young and old animals. The changes in miRNA expression described in this study that relate to age, may play a role in the impaired differentiation capacity of older muscle stem cells.